Rapid Development of a Tool for Prioritizing Patients with Coronavirus Disease 2019 for Intensive Care. (12th March 2021) - Roy, Melyssa; Hansen, Paul; Sullivan, Trudy; Ombler, Franz; Kiore, Mathew; Stapleton, Andrew; Carr, Craig
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To explain and demonstrate a new approach for rapidly developing a decision-support tool for prioritizing patients with coronovirus 2019 disease for admission to ICUs. Design: An expert group used multi-criteria decision analysis methods to specify criteria and weights, representing their relative importance, for prioritizing patients with coronovirus 2019 disease with respect to likely clinical benefit. Specialized multi-criteria decision analysis software, implementing the "Potentially All Pairwise RanKings of all possible Alternatives" method to determine the weights, was used. Social equity considerations for prioritizing patients were also identified as important. Setting: The prioritization tool was developed in New Zealand. Subjects: An expert group comprising specialists from intensive care medicine and nursing, Māori (New Zealand's indigenous population) health, infectious diseases, and neonatology was formed. The group's work was supported by health economists and decision analysts and overseen by an ethicist and a senior representative from the New Zealand Ministry of Health. Interventions: Multi-criteria decision analysis to create a prioritization tool. Measurements and Main Results: The prioritization tool comprised eight criteria with respect to likely clinical benefit. In decreasing order of importance (weights in parentheses): Sequential Organ Failure Assessment score (15.7%), preexisting cardiovascular conditions (15.7%), functional capacity (15.7%), age (12.4%), preexisting respiratory conditions (11.1%), immunocompromised (11.1%), body mass index (9.2%), and other relevant medical conditions (9.2%). Two social equity considerations were also included in the overarching decision framework to be used alongside the clinical criteria: prioritizing Māori and Pacific people (and, potentially, other at-risk groups), and healthcare and other frontline workers. Conclusions: The criteria and weights in the prioritization tool can be easily revised as new evidence emerges. The approach for developing the tool could be used in other countries whose ICUs are at risk of being overwhelmed by the coronavirus disease 2019 pandemic to rapidly develop their own prioritization tools. In the event that future crises threaten to overload ICUs, other prioritization tools could also be rapidly developed.